TIZ 6938 - Final Project and Internal Internship Report - Nurul Ilyani, Abdullah Hasnan (College of Arts and Sciences, 2008)
Syaily Enterprise is a partnership company owned by two person and has been registered in year 2006. Starting July 2007, Syaily Enterprise has executed a project called kioskSerindIT in order to fulfill the sales term of RM 100,000.00. In March 2008, Syaily Enterprise has successfully fulfilled the term by gaining RM 200,000.00 of sales.